2017
DOI: 10.1002/aenm.201700920
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Carbon Battery Based on Potassium‐Ion Electrolyte

Abstract: with SIBs, potassium-ion batteries (KIBs) deliver a higher working voltage due to the lower redox potential of K + /K (−2.92 V vs SHE) than that of Na + /Na (−2.71 V vs SHE). [14] In addition, K + has been demonstrated to be reversibly intercalated/ deintercalated into graphite anode, while very limited amounts of Na + could. [14] However, as the research on KIBs is still at the infancy stage, the mechanisms at an atomic scale and interfaces are unclear. In addition, owing to the large size of K + that would c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
182
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 256 publications
(190 citation statements)
references
References 43 publications
(123 reference statements)
2
182
0
2
Order By: Relevance
“…In their experiments, they found that some commonly observed anions couldr eversibly intercalate into a graphite layer at high potential, such as AlCl 4 À ,F SI À ,P F 6 À , BF 4 À ,a nd C 6 H 5 CO 2 À (benzonate). [82][83][84][85][86][87] An alternative version of the dual-ion battery was also reported. However,t he dual-ion energy storagew ent almost uninvestigated for nearly ad ecade, duringw hich time only af ew studies focused on this promising aspect.…”
Section: Aluminummentioning
confidence: 99%
“…In their experiments, they found that some commonly observed anions couldr eversibly intercalate into a graphite layer at high potential, such as AlCl 4 À ,F SI À ,P F 6 À , BF 4 À ,a nd C 6 H 5 CO 2 À (benzonate). [82][83][84][85][86][87] An alternative version of the dual-ion battery was also reported. However,t he dual-ion energy storagew ent almost uninvestigated for nearly ad ecade, duringw hich time only af ew studies focused on this promising aspect.…”
Section: Aluminummentioning
confidence: 99%
“…The usage of the aluminum anode and graphite cathode significantly reduced the cost of DIBs. To further reduce the cost of DIBs, completely lithium‐free systems based on other low‐cost cations, such as Na + , K + , Ca 2+ , Al 3+ were also reported in recent years (Table ). Furthermore, in consideration of the future requirements of energy storage devices, such as high safety, flexibility, wearability, the new DIBs should be combined with all‐solid‐state batteries, organic batteries, and other aforementioned batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The development of ECs is restricted by low energy density [6][7][8]. On the contrary, the other type of crucial energy-storage devices such as electrochemical batteries including Li-ion [9,10], Li-O 2 [11,12], Li-S [13], Na-ion [14,15] and double-ion batteries [16,17], etc., have been extensively accepted to be durable and of high energy density to supply prolonged operation in a majority of electronic equipments. However, owing to slow insertion/extraction dynamics, these batteries show unsatisfactory power output.…”
Section: Introductionmentioning
confidence: 99%